Happily ever Amish [large type] - Gray, Shelley Shepard (Gray, Shelley Shepard. Amish of Apple Creek, 2023)
"Addie Holmes is Apple Creek's resident wallflower. She is kind and giving and has a lot to be grateful for. But she is full of self-doubt because her parents did not want her and gave her to her grandmother to raise. Now her life seems to be just hard work and loneliness. Wary of romance, Addie assumes no man will look beyond her glasses and her tendency to talk to her rescue donkey, Snickers -- until the day she receives a note from a secret admirer. A prank, most likely. But then, a second note arrives . . . It's not that Daniel Miller doesn't like Addie, he just doesn't want to court her. He doesn't really know her. Yet when he learns she's been teased because she's never had a beau, he decides to send a little note of encouragement. One note leads to another. And when Addie begins replying with thoughtful messages of her own, he's struck by her sweetness and warmth. Soon, what began as a sympathetic gesture becomes something deeper. Daniel fears revealing the truth, but with courage, faith -- and a helping hand from their close-knit community -- Apple Creek's most unlikely couple may find their path to happiness . . ."--